Murvadi Agada-QC Analysis, Method of Preparation & its Uses in Current Scenario - Hiremath, Rudramma R; Digra, Roshi (International Research Journal of Ayurveda & Yoga, 2022)
Murvadi Agada is a unique and useful formulation, which is specifically prescribed for Agni Vikara’s. It is a compound herbal preparation that is explained under the context of “Garopahat Paavaka” i.e. a condition which is a result of impaired Agni caused due to administration of Gara visha. The formulation is a sole contribution of Asthanga Kara’s which is not explainecd elsewhere. Murvadi Agada has to be administered with Anupanas like Ushana Jala, Takra, Mastu and Amla Rasa Dravyas. Gara visha condition in present era can arise due to addition of toxic substances like animal excreta, toxic medicines, viruddhaaushadhi etc to food substances. In current scenario all the junk food, colouring agents, food additives, preservatives, packed food items and drinks can be taken as Gara Visha. This may produce Agni Vikara’s (digestive disorders) like Sthoulya, Arsha, Attisara, Udara Rogas etc. Murvadi Agada administered with proper Anupana can help in these diseases.